Effect of Aqueous Extract of Hibiscus Sabdariffa on Cadmium Chloride-Induced Neurotoxicity in Male Wistar Rats (Nigerian Journal of Physiological Sciences, 2025)
This study investigated the neurologic effect of aqueous extract of Hibiscus sabdariffa on cadmium chloride-induced neurotoxicity in wistar rats. Thirty male wistar rats were grouped accordingly; Group A: control, Group B-F: CdCl2 0.3ml; H. sabdariffa 1.5ml; CdCl2 + H. sabdariffa 1.0ml; CdCl2 + H. sabdariffa 1.5ml; CdCl2 + H. sabdariffa 2ml, respectively. Gas chromatography coupled to flame ionization detector (GC-FID), total antioxidant capacity (TAC) and mineral analysis of H. sabdariffa was done to reveal the bioactive agents in the plant sample. Oxidative stress, muscle function markers and plasma electrolytes were assayed. Phytochemical screening revealed alkaloids, phytate, anthraquinone and flavonoids. The mineral analysis revealed predominantly, Mn, Ca, K and Fe. The biochemical results were in comparison with control and statistically significant at 95% confidence interval. There was an increase in SOD, CAT, GSH, GR and GPx in groups C-F, MDA decreased in group C, E and F while PC decreased in group C and F. There was a decrease in plasma creatine kinase in groups C to F and increase in AChE in group C. Ca and K levels had no significant change (P